The Influence of Leading Sector Grdp And Special Autonomy Funds on Poverty In Aceh Province - Aulianur, Ahlul; Effendi, Rustam; Abrar, Muhammad (Mutiara: Multidiciplinary Scientifict Journal, 2023)
The purpose of this study is to analyze the effect of leading sector GRDP and special autonomy funds on poverty in Aceh Province. This study employs quantitative techniques by regressing quarterly time series data for the years 2010 to 2022. The agriculture, mining, trade, transportation, real estate, administration, health services sectors are the leading sectors obtained from the Location Quotient (LQ) calculation. The results showed that the agriculture, trade and transportation sectors have a negative effect on poverty. the real estate and administration sector has a positive effect on poverty. Meanwhile, the mining and health services sectors have no effect on poverty. Special autonomy funds have a negative effect on poverty in Aceh Province. The agriculture, trade, transportation sectors are considered as sectors that should be the focus of development and funding from the allocation of special autonomy funds by the Government of Aceh.